Mixed Grazing Increases Abundance of Arbuscular Mycorrhizal Fungi in Upland Welsh Grasslands - Annie Lesley Buckle; Felicity Victoria Crotty; Philip L. Staddon (Soil Systems)
Grasslands play a crucial role in exchanges between global ecosystems and the atmosphere and form an integral part of the agricultural industry. Arbuscular mycorrhizal fungi (AMF) are mutualistic symbionts of most grassland plant species and thereby influence the functional capacity of grassland systems. Agricultural grasslands are primarily used for livestock farming and are subjected to various management practices designed to increase production, but which also alter both plant and soil communities in the process. This research investigated the effects of a selection of management practices and environmental factors on the presence and abundance of AMF in upland Welsh grasslands. The aim was to identify how these management practices affected the abundance of AMF, assessed through microscopic observations of four AMF structures: spores, hyphae, vesicles and arbuscules. The results suggest grazing sheep and cattle together had the highest overall influence on AMF abundance compared to grazing sheep or cattle separately. High plant diversity correlated with high arbuscule and vesicle abundance, but conversely, the application of lime reduced vesicle abundance. These findings offer new insights into the effects of management practices on AMF. Mixing livestock, increasing plant diversity and reducing lime applications are shown here to improve the abundance of AMF and could, therefore, help to inform sustainable farm management decisions in the future.